On the ion and electron temperature recovery after the ELM-crash at ASDEX upgrade. (January 2019) - Cavedon, M.; Dux, R.; Pütterich, T.; Viezzer, E.; Wolfrum, E.; Dunne, M.; Fable, E.; Fischer, R.; Harrer, G.F.; Laggner, F.M.; Mink, A.F.; Plank, U.; et al.
Abstract: The access to fast measurements, i.e. Δt ≈ 100 µs, of the ions and the electrons during an entire edge localized cycle (ELM) reveals asymmetries in the recovery of the maximum edge gradients. Different magnetic fluctuations are found to correlate with the saturation of the edge ion temperature ( Ti ), electrons temperature ( Te ) and density ( ne ) gradients. In particular, while ∇ Ti and ∇ ne clamp roughly 3.0 ms after the ELM-crash together with the onset of mid-frequency ( f ≲ 50 kHz) magnetic fluctuations, ∇ Te recovers to the pre-ELM conditions only after 7.0 ms and saturates with the appearance of high frequency fluctuations ( f ≈ 200 kHz). The effect of electron temperature gradient modes (ETGs) and of energy losses induced by ionization of neutrals are discussed as possible reasons for the delayed recovery of ∇ Te . The onset and the suppression of ETGs qualitatively follow the requirements of an increased electron heat transport. However, gyro-kinetic simulations are necessary to quantify the impact of ETGs. On the other hand, the impact of the neutral ionization during the density build-up as an electron energy loss channel is measured to be small compared to the total electron energy. The dominant terms in the electron energy balance are instead the radiative power and the ion-electron heat exchange.